Arterial carbon dioxide tension has a non-linear association with survival after out-of-hospital cardiac arrest: A multicentre observational study. (May 2021) - Mckenzie, Nicole; Finn, Judith; Dobb, Geoffrey; Bailey, Paul; Arendts, Glenn; Celenza, Antonio; Fatovich, Daniel; Jenkins, Ian; Ball, Stephen; Bray, Janet; Ho, Kwok M.
Abstract: Purpose: International guidelines recommend targeting normocapnia in mechanically ventilated out-of-hospital cardiac arrest (OHCA) survivors, but the optimal arterial carbon dioxide (PaCO2 ) target remains controversial. We hypothesised that the relationship between PaCO2 and survival is non-linear, and targeting an intermediate level of PaCO2 compared to a low or high PaCO2 in the first 24-h of ICU admission is associated with an improved survival to hospital discharge (STHD) and at 12-months. Methods: We conducted a retrospective multi-centre cohort study of adults with non-traumatic OHCA requiring admission to one of four tertiary hospital intensive care units for mechanical ventilation. A four-knot restricted cubic spline function was used to allow non-linearity between the mean PaCO2 within the first 24 h of ICU admission after OHCA and survival, and optimal PaCO2 cut-points were identified from the spline curve to generate corresponding odds ratios. Results: We analysed 3769 PaCO2 results within the first 24-h of ICU admission, from 493 patients. PaCO2 and survival had an inverted U-shape association; normocapnia was associated with significantly improved STHD compared to either hypocapnia (<35 mmHg) (adjusted odds ratio [aOR] 0.45, 95% confidence interval [CI] 0.24−0.83) or hypercapnia (>45 mmHg) (aOR 0.45, 95% CI 0.24−0.84). Of the twelve predictors assessed, PaCO2 was the third most important predictor, and explained >11% of the variability in survival. The survival benefits of normocapnia extended to 12-months. Conclusions: Normocapnia within the first 24-h of intensive care admission after OHCA was associated with an improved survival compared to patients with hypocapnia or hypercapnia.